PENERAPAN TOTAL QUALITY MANAGEMENT ( TQM ) UNTUK PENGENDALIAN TOTAL KUALITAS DALAM GUDANG LOGISTIK BERAS BULOG DI KOTA SORONG - MAHMUD, FADILA MAHMUD; Gani, Mardhiah; Muliati, Zulfa; Hahury, Sanny; Tajuddin, Tamrin (Universitas Muhammadiyah Sorong, 2024)
This research aims to find research gaps by using Publish or Perish (Pop) to obtain data from the Google Scholar website and visualize it via Vosviewer software with the results of developments in research topics and issues centered on